KUALITAS GENTENG TANAH LIAT DENGAN CAMPURAN SERBUK KACA - Faiz Mudhofir; Sulhadi Sulhadi; Mahardika Prasetya Aji (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
The growth of human population is proportional to its needs. Fulfilling daily needs increases the amount of household waste. Glass waste is one of the waste that needs to be utilized optimally. Therefore it is necessary to invent the utilization of glass waste. One of its innovative forms is the use of glass powders for mixed materials on the manufacturing of clay tile home industry. Therefore, in this study researchers will use glass waste as a mixture of tile with mixed compositions of 0%, 5%, 10%, 15%, and 20% of the overall mass of clay tile. The quality of this tile will be compared between the normal and mixed one, it would be seen from the variable water absorbtion and tile strength. The results stated that the more mixture of glass powder, the tile has a smaller porosity / has a lower water absorbtion. The best mixture was obtained in a 15% mixture of 8.57%. The addition of the glass powder affects the tensile force of the clay particles in the tile, so in certain compositions it is possible to increase the compressive strength but in the excess composition it reduces the compressive strength.Keywords: clay tile, glass powder, compressive strength, absorbtion.